Prevalence and Progression of Newly Diagnosed Diabetes Mellitus in COVID-19 patients at Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2024)
Background: During the follow-up of Covid-19 patients during the Corona pandemic, an increase in the numbers of people with newly diagnosed diabetes mellitus (NDDM) and its severe course was observed in a number of patients. It was assumed that there is a relationship between infection with Covid-19 and development of diabetes in those not previously known to have diabetes. It was suggested that they should be followed up to understand the course of diabetes following Covid-19 infectionObjectives: Study the incidence of newly discovered diabetes among Covid-19 patients. Then study the development and progression of the disease by following them for 3 months after diagnosis. And the study of the prognostic factors that accompanied the newly discovered diabetes.Materials and Methods: A prospective cohort study conducted in the isolation department of Tishreen University Hospital in Latakia between May 2022 and May 2023. The study included 209 COVID-19 patients diagnosed with a positive PCR and not previously known to have diabetes. Glycated hemoglobin was measured on those who developed hyperglycemia ​​in order to study the prevalence of newly diagnosed diabetes in the study group.Results: The incidence of newly diagnosed post-COVID-19 diabetes was (16.3%), while the incidence of new-onset post-COVID-19 diabetes was (11.5%). The recovery rate after a 3-month follow-up in patients with new-onset diabetes was (27.3%). Mean BMI was higher in the NDDM group compared to non-diabetics. The lymphocyte count and WBC were lower with a statistically significant difference in the NDDM group compared to the non-diabetic group. The severity of infection on chest CT, body mass index, family history, need for oxygen, and duration of hospitalization were higher in patients with new-onset diabetes who have continued on the treatment of diabetes.Conclusions: COVID-19 infection can cause new-onset diabetes mellitus and ketoacidosis in some cases and without a history of diabetes. Upon follow-up for three months, one-third of the cases recoverd without the need for treatment. Mean body mass index, the severity of the infecton on chest CT scan, and decreased lymphocyte count were an important prognostic factor in the development of new-onset diabetes.